Pengujian Sah Tidaknya Penetapan Tersangka dalam Kerangka Praperadilan - Rizka Fakhry Alfiananda (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
A pretrial construction as it has been regulated in the IndonesianCriminalProcedure Code had instantly changed after the Constitutional Court decisionNumber : 21/PUU-XII/2014 that being announced on April 28, 2015. Thepretrial construction was initially authorized only to examine and decide the validity ofarrest and detention, the validity of investigation and prosecution termination, and thedemand for compensation or rehabilitation. The authority of the pretrial by a quodecision was then expanded by adding an examination on the validity of inquiry, thevalidity of confiscation, and the validity of suspect determination. Although a quodecision is reputed tohave exceeded the authority of the Constitutional Court because itis judged of creating a new norm, a quo decision remains final and tied so that it shouldbe considered as a complement to the Indonesian Criminal Procedure Code.